Pesimismo antropológico, comercio y economía: de Hobbes a Montesquieu: Anthropological Pessimism, Commerce, and Economy: from Hobbes to Montesquieu - Leiva, Matias (Universidad del Zulia, 2021)
In this article we will approach Hobbes’ anthropological considerations about the new ways of understanding human nature in the modern era and, therefore, economy and commerce. We will try to show the reception of Hobbes’ anthropology in Montesquieu and prove it was used as base for the construction of a model of society based on commerce. Then, we will argue that, in Montesquieu’s theory, it was discovered that passions could be used so they may have a positive effect on economy and commercial development. Finally, we will consider the problems and difficulties that rise from such a proposal and the anthropological implications it has.